Prevalence and associated factors of hypertension among adults in Gadarif in eastern Sudan: a community-based study - Saeed M. Omar; Imad R. Musa; Osman E. Osman; Ishag Adam (BMC, 2020)
Abstract Background Hypertension is becoming an increasingly common health issue worldwide, especially in countries in Sub-Saharan Africa. Hypertension is the leading risk factor for premature death and disability worldwide, and it is the leading risk factor for mortality from cardiovascular diseases worldwide. The data on hypertension in Sudan that has been published is limited. We conducted this study to assess the prevalence of hypertension and its associated risk factors. Methods A multistage sampling survey was conducted in Gadarif, Eastern Sudan, from January to May 2018 to investigate the prevalence of hypertension and associated factors in adults in Eastern Sudan. The World Health Organization (WHO) three-level stepwise approach questionnaire was used to gather sociodemographic characteristics (age, sex, height, weight marital status, education level, smoking habit, alcohol consumption habit, and family history of hypertension). Hypertension was defined as the presence of an average blood pressure of ≥140/90 mmHg or the reported use of anti-hypertensive medications for high blood pressure. Results A total of 600 participants (mean age: 44.9 years) were enrolled in this study. Four hundred twenty-two (70.3%) participants were women, and 196 (32.7%) participants were obese. Of the 600 enrolled participants, 245 (40.8%) individuals had hypertension, 44 (7.3%) had been previously diagnosed with hypertension, and 201 (33.5%) were newly diagnosed with hypertension. A logistic regression analysis showed no significant associations across the education level, marital status, overweight and hypertension factors. However, an older age (adjusted OR = 3.20, 95% CI = 2.28-4.51, P < 0.001) and obesity (adjusted OR = 2.41, 95% CI = 1.57-3.69, P < 0.001) were associated with the presence of hypertension. Conclusion There is a high rate of hypertension in Eastern Sudan, especially among older and obese individuals. Preventive measures, such as dietary measures, should be implemented.